Birth cohorts, marriage patterns, and contraceptive methods used among women in contemporary Myanmar - Nyein Chan; Yothin Sawangdee; Umaporn Pattaravanich; Charamporn Holumyong; Aphichat Chamratrithirong (College of Public Health Sciences, Chulalongkorn University, 2020)
Purpose - The total fertility rate in Myanmar stands low in comparison to neighboring countries. This decrease in the birth rate will lead to a decline in the number of young Burmese in the future, an issue that is of concern to the Myanmar government. The purpose of this study was to review the contributing factors to marriage and birth rates and to also review the use of contraception among married women. Design/methodology/approach - This quantitative research study was based on cross-sectional secondary data available from the Myanmar Demographic and Health Survey 2015-2016. The study sample included 6,138 women of reproductive age. Findings - The proportion of unmarried women and the mean age at the first marriage date in the early cohort was higher than that of the women who were born in the later cohort. The study shows that birth cohort, female labor force participation, migration, wealth index, and media exposure are significant in explaining marriage types and patterns (p < 0.05). The injection and the pill were the most popular contraceptive methods for both cohorts. Other methods such as intrauterine devices, implants, and condoms were not as popular. Originality/value - This paper presents the birth cohort, female labor force participation, migration, wealth index, and media exposure as key factors for determining the timing of marriage.